Investigating the Effect of Leadership Styles on Conflict Resolution Methods and Attitudes of Employees of Yazd Electricity Distribution Company - CHABOKINEZHAD, MOHAMMAD HOSSEIN (The journal of contemporary issues in business and government, 2021)
It seems leadership style is related to and influenced by behavioral factors such as conflict resolution styles and employee attitudes. Therefore, this research investigates the effect of leadership styles on conflict resolution styles and employee attitudes with regard to the moderating role of demographic variables in the Yazd Electricity Distribution Company. This research is a descriptive and correlational research in terms of method, practical in terms of purpose and survey in terms of data collection method. In this research the questionnaire was taken from the article of Karadaka et al. (2015) and Quintana et al. (2015) with 46 questions designed on the Likert scale. The statistical population of this study is the employees of Yazd Electricity Distribution Company. Using simple random sampling, 140 questionnaires were distributed among the employees. The reliability of the questionnaire, which was calculated by Cronbach's alpha method, is equal to 0.889. The validity of the test was also confirmed by content and structure methods. Using structural equation modeling and partial least squares approach with the help of PLS software, the results of testing the research hypotheses showed that leadership styles have a significant and positive effect on conflict resolution styles and employee attitudes. Also, the demographic variable has a moderating role in the relationship between leadership styles and attitudes among employees of Yazd Electricity Distribution Company.